Frontiers in Bioenergy and Biofuels 2017
DOI: 10.5772/66357
|View full text |Cite
|
Sign up to set email alerts
|

Use of Corn Dried Distillers Grains (DDGS) in Feeding of Ruminants

Abstract: Bioethanol is the product of fermentation of starch contained in renewable resources, such as corn, wheat, rye and rice. Depending on the technology used for its production, dried distillers decoction may exist in diferent forms: dried distillers grain (DDG); dried distillers grain with solubles (DDGS) and high-protein dried distillers grains (HPDDG), as well as wet distillers grain (WDG), wet distillers grain with solubles (WDGS), and high-protein wet distillers grains HPWDG). Research conducted in recent yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
2
12
0
1
Order By: Relevance
“…Compared with CON, the BYP concentrate contained less saturated FA (SFA; 36.0 vs. 25.4%, respectively). This is in agreement with previous studies in which diets including DDGS, DCP, or EOC were tested [8][9][10], and it was attributed to the high proportion of unsaturated FA in DDGS, DCP, and EOC [5,6,30].…”
Section: Resultssupporting
confidence: 93%
“…Compared with CON, the BYP concentrate contained less saturated FA (SFA; 36.0 vs. 25.4%, respectively). This is in agreement with previous studies in which diets including DDGS, DCP, or EOC were tested [8][9][10], and it was attributed to the high proportion of unsaturated FA in DDGS, DCP, and EOC [5,6,30].…”
Section: Resultssupporting
confidence: 93%
“…Compared with the control, BYP concentrate had greater content of oleic (C18:1 cis-9) and linoleic (C18:2 cis-9,cis-12) acids and lower content of lauric (C12:0), myristic (C14:0), and palmitic (C16:0) acids, which is in agreement with previous results indicating that the inclusion of olive cake in the diet usually increases the amount of oleic acid (Molina-Alcaide et al, 2010;Luciano et al, 2013). Furthermore, about 80% of FA in DDGS are unsaturated (Pecka-Kielb et al, 2017), and the FA in citrus pulp are mainly oleic, linoleic, linolenic (C18:3), palmitic, and stearic acids (C18:0; Bampidis and Robinson, 2006), which might have contributed to the differences observed in FA profile of the 2 concentrates. The most abundant FA in alfalfa hay were palmitic, linoleic, and linolenic acids (24.7, 21.9, and 34.6% of total FA, respectively), which is in agreement with previous results (Molina-Alcaide et al, 2010;Romero-Huelva et al, 2017).…”
Section: By-products and Concentrates Compositionsupporting
confidence: 92%
“…Milk yield response to DDGS inclusion in the diet has also been positive in dairy cows (Hollmann et al, 2011), and an increase in milk protein and lactose yield has been reported in several studies (Anderson et al, 2006;Kleinschmit et al, 2006;Janicek et al, 2008). In contrast, no effect on milk yield was observed in sheep fed 20% of DDGS (Pecka-Kielb et al, 2017), and even a reduction in milk protein, fat, and TS has been observed by Radunz et al (2011). The results of the influence of olive cake feeding on milk yield and composition are also controversial.…”
Section: Milk Yield and Compositionmentioning
confidence: 99%
“…This product contains the fat, protein, and minerals of the corn, making it suitable feed or supplement for livestock such as cows, sheep, swine, poultry, rabbits, goats, fish, horses, dogs, and other animals. In 2018–2019, 44 million metric tons of DDGS was produced, with over 11 million tons exported to over 97 countries (Pecka‐Kiełb et al., 2017; U.S. Grains Council, 2018). There is concern that the antibiotics may still be present and biologically active in DDGS, causing the livestock to be unintentionally consuming large amounts of antibiotics (Duelge et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This product contains the fat, protein, and minerals of the corn, making it suitable feed or supplement for livestock such as cows, sheep, swine, poultry, rabbits, goats, fish, horses, dogs, and other animals. In 2018-2019, 44 million metric tons of DDGS was produced, with over 11 million tons exported to over 97 countries (Pecka-Kiełb et al, 2017;U.S. Grains Council, 2018).…”
Section: Introductionmentioning
confidence: 99%